Autoimmune polyglandular syndrome, type 2 associated with myasthenia gravis - Pejin Radoslav; Stokić Edita; Novković Mile; Banić-Horvat Sofija; Cvijanović Milan (Vojnosanitetski Pregled)
Introduction. Autoimmune polyglandular syndrome type 2 is defined as adrenal insufficiency associated with autoimmune primary hypothyroidism and/or with autoimmune type 1 diabetes mellitus, but very rare with myasthenia gravis. Case report. We presented a case of an autoimmune polyglandular syndrome, type 2 associated with myasthenia gravis. A 49-year-old female with symptoms of muscle weakness and low serum levels of cortisol and aldosterone was already diagnosed with primary adrenal insufficiency. Primary hypothyroidism was identified with low values of free thyroxine 4 (FT4) and raised values of thyroidstumulating hormone (TSH). The immune system as a cause of hypothyroidism was confirmed by the presence of thyroid antibodies to peroxidase and TSH receptors. Myasthenia gravis was diagnosed on the basis of a typical clinical feature, positive diagnostic tests and an increased titre of antibodies against the acetylcholine receptors. It was not possible to confirm the immune nature of adrenal insufficiency by the presence of antibodies to 21- hydroxylase. The normal morphological finding of the adrenal glands was an indirect confirmation of the condition as well as the absence of other diseases that might have led to adrenal insufficiency and low levels of both serum cortisol and aldosterone. Hormone replacement therapy, anticholinergic therapy and corticosteroid therapy for myasthenia gravis improved the patient’s general state of health and muscle weakness. Conclusion. This case report indicates a need to examine each patient with an autoimmune disease carefully as this condition may be associated with another autoimmune diseases.